1996
DOI: 10.1002/(sici)1096-9918(199603)24:3<204::aid-sia90>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PTFE on Silicon Wafer Tribological Transfer Films by XPS, Imaging XPS and AFM

Abstract: Atomic force microscopy (AFM) shows that PTFE‐on‐silicon wafer tribological transfer films consist of narrow ribbons of PTFE, <1 μm wide and <10 nm high, aligned with the film draw direction. Within the ribbons the PTFE molecular chains are also aligned with the draw direction. Such materials are of interest as substrates for the epitaxial crystallization of polymers and small molecules. X‐ray photoelectron spectroscopy demonstrates that the amount of PTFE put down increases with deposition temperature and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…It has been well established that under slow (< 10 mm Á s À1 ) sliding speeds, the transfer of PTFE can provide an aligned, thin, transfer film for low shear sliding. [85][86][87][88][89] The relationship between transfer film thickness and wear rate suggests that extremely thin and uniform films of PTFE might also be very wear resistant. Recently, experiments were conducted to quantify the tribological properties of model PTFE films to test the hypothesis that thin aligned PTFE films can support low wear sliding.…”
Section: Quantifying Transfer Filmsmentioning
confidence: 99%
“…It has been well established that under slow (< 10 mm Á s À1 ) sliding speeds, the transfer of PTFE can provide an aligned, thin, transfer film for low shear sliding. [85][86][87][88][89] The relationship between transfer film thickness and wear rate suggests that extremely thin and uniform films of PTFE might also be very wear resistant. Recently, experiments were conducted to quantify the tribological properties of model PTFE films to test the hypothesis that thin aligned PTFE films can support low wear sliding.…”
Section: Quantifying Transfer Filmsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] AFM is especially suited to polymer analysis due to the low applied forces in contact mode, which can be further reduced by using tapping mode. These low forces allow the film surface to be imaged without modification by the force of the AFM tip on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 Identification of the physical and chemical nature of these interactions has been of great academic as well as commercial importance for more than 5 decades. [1][2][3][4][5][6][7][8][9][10][11][12] Makinson and Tabor studied the transfer and friction of polytetrafluoroethylene (PTFE) sliding on glass using optical and scanning electron microscopic techniques, where they demonstrated that PTFE could be transferred onto other surfaces during sliding motion. 1 They also identified two frictional regimes (low and high) depending on both the temperature at which the sliding was carried out and the speed of the sliding motion.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Although many other studies on PTFE transfer to another solid surface have been published, most have focused on improvement of the physical properties of surfaces, i.e., achieving lower friction coefficients and wear rates. [11][12][13][14][15][16][17][18][19] However, the nature of those interactions at the atomic scale has not been completely understood. To this end, applying computational chemistry methods as a tool for analyzing the mechanism of friction and transfer film formation has recently been reported.…”
Section: Introductionmentioning
confidence: 99%